Betrayal trauma and child symptoms: The role of emotion. Issue 2 (14th March 2016) - Gagnon, Kerry L.; DePrince, Anne P.; Chu, Ann T.; Gorman, McKayla; Saylor, Megan M.
ABSTRACT: Both mothers' and children's exposures to interpersonal violence—including betrayal traumas—are linked with heightened risk for children developing internalizing and externalizing symptoms. Despite this association, little research has examined additional factors that may explain this risk, such as emotion skills. The current study examined the relationship between mother–child emotion understanding abilities and use of emotion language on a behavioral facial affect perception task and betrayal trauma exposure in relation to child internalizing/externalizing symptoms. The sample included 47 ethnically diverse female guardians (ages 25–51 years old; M age = 37.7) and their children (ages 7–11 years old; M age = 9.1). Results indicated that maternal provision of a spontaneous, unprompted reason for emotions during the facial affect perception task was significantly associated with lower child internalizing/externalizing symptoms when both mothers' and children's betrayal trauma histories were controlled. The results suggest that emotion skills (in particular, the way mothers talk about emotions) warrant greater attention in research on the development of child internalizing/externalizing problems.